Pengukuran suhu air menggunakan Fiber Bragg Grating - Irwan Kustianto; Retno Wigajatri Purnamaningsih; Sasono Rahardjo; Maratul Hamidah; Muhammad Yusha Firdaus (Postgraduate, University of Mataram, 2023)
Temperature measurement in water is crucial for various applications and technological advancements. Fiber Bragg Grating (FBG) sensors have shown significant potential in measuring water temperature, with advantages in accuracy, reliability, and resistance to extreme environmental conditions. In this study, we conducted a series of experiments to measure water temperature in the range of 4 to 25 degrees Celsius using FBG sensors. Through two experimental analyses of the FBG sensor's response to water temperature changes, we found that the sensitivity of the FBG sensor we used was 0.0101 nm/Â°C. The results of this research demonstrate that FBG sensors are capable of measuring water temperature with high sensitivity, accuracy, and stability.